Design of Pond Water Turbidity Monitoring System in Arduino-based Catfish Cultivation to Support Sustainable Development Goals 2030 No.9 Industry, Innovation, and Infrastructure - Anggara Trisna Nugraha; Dadang Priyambodo (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2020)
Catfish is one of the fishery products favored by the community because of its high protein. So that Catfish is one of the fish that is the center of business for fish farmers. The pond conditions used by Catfish farmers are generally still conventional. So that the maintenance of clean water in ponds is still done manually and even escapes attention. Water conditions will affect the health and productivity of Catfish. In order to achieve the optimum conditions in the third media, a control system consisting of three types of sensors will be used, namely Flowmeter, LDR sensor and LM35 sensor. The flowmeter sensor is used to regulate the flow of water, the LDR sensor functions as a receiver that is used to detect the level of turbidity of water based on how much light enters the water (turbidity). Meanwhile, the LM35 sensor functions to detect the temperature in the media so that the optimum condition for Catfish based on temperature parameters is around 22 - 32 ° C